Comparing the cost-effectiveness of linezolid to trimethoprim/sulfamethoxazole plus rifampicin for the treatment of methicillin-resistant Staphylococcus aureus infection: a healthcare system perspective. (September 2017) - von Dach, E.; Morel, C.M.; Murthy, A.; Pagani, L.; Macedo-Vinas, M.; Olearo, F.; Harbarth, S.
Abstract: Objective: Few industry-independent studies have been conducted to compare the relative costs and benefits of drugs to treat methicillin-resistant Staphylococcus aureus (MRSA) infection. We performed a stochastic cost-effectiveness analysis comparing two treatment strategies—linezolid versus trimethoprim-sulfamethoxazole plus rifampicin—for the treatment of MRSA infection. Methods: We used cost and effectiveness data from a previously conducted clinical trial, complementing with other data from published literature, to compare the two regimens from a healthcare system perspective. Effectiveness was expressed in terms of quality-adjusted life-years (QALYs). Several sensitivity analyses were performed using Monte Carlo simulation, to measure the effect of potential parameter changes on the base-case model results, including potential differences related to type of infection and drug toxicity. Results: Treatment of MRSA infection with trimethoprim-sulfamethoxazole plus rifampicin and linezolid were found to cost on average €146 and €2536, and lead to a gain of 0.916 and 0.881 QALYs, respectively. Treatment with trimethoprim-sulfamethoxazole plus rifampicin was found to be more cost-effective than linezolid in the base case and remained dominant over linezolid in most alternative scenarios, including different types of MRSA infection and potential disadvantages in terms of toxicity. With a willingness-to-pay threshold of €0, €50 000 and €200 000 per QALY gained, trimethoprim-sulfamethoxazole plus rifampicin was dominant in 100%, 96% and 85% of model iterations. A 95% discount on the current purchasing price of linezolid would be needed when it goes off-patent for it to represent better value for money compared with trimethoprim-sulfamethoxazole plus rifampicin. Conclusions: Combined treatment of trimethoprim-sulfamethoxazole plus rifampicin is more cost-effective than linezolid in the treatment of MRSA infection.